Dosing of Intravenous Tocilizumab in a Real-World Setting of Rheumatoid Arthritis: Analyses from the Corrona Registry. Issue 1 (June 2016) - Pappas, Dimitrios; John, Ani; Curtis, Jeffrey; Reed, George; Karki, Chitra; Magner, Robert; Kremer, Joel; Shewade, Ashwini; Greenberg, Jeffrey
ABSTRACT Introduction In the United States, the recommended starting dose of intravenous tocilizumab (TCZ) is 4 mg/kg every 4 weeks, with an increase to 8 mg/kg based on clinical response for patients with moderate to severe rheumatoid arthritis; however, data on how TCZ dose is escalated in real life are missing. The objective of this analysis was to describe patterns of early intravenous TCZ dose escalation in a real-world setting using data from the Corrona registry. Methods All patients enrolled in the comparative effectiveness substudy (CERTAIN) nested within Corrona who initiated TCZ and completed 3- and 6-month study visits were eligible for inclusion. Patients who initiated TCZ 4 mg/kg were categorized into 1 of 2 groups: those who remained on TCZ 4 mg/kg at 3 months (Group 1) and those who escalated to TCZ 8 mg/kg by or at 3 months (Group 2). Changes in clinical disease activity measures were provided. Results Of the 213 patients who were eligible for analysis, 86 (40.4%) remained on their initial dose of TCZ 4 mg/kg (Group 1) and 110 (51.6%) were escalated to TCZ 8 mg/kg by or at 3 months (Group 2). Baseline demographic and clinical characteristics were similar between the 2 groups; except in Group 2, patients were older (58.3 vs. 54.0 years) and a lower proportion was female (75.5% vs. 89.4%) than in Group 1. Significant improvements in disease activity measures were observed at 3 and 6 months in both groups, with the majority of patients in both groups achieving moderate or good European League Against Rheumatism response. Conclusion Real-world data demonstrated that physicians escalate TCZ dose at varying frequencies. The ability to administer TCZ in varying doses allows physicians to tailor TCZ therapy to disease activity. Trial registration ClinicalTrials.gov identifier, NCT01625650.